Avianomics: The Beginning at the End - Mary Komp; Rebecca Bowie; Jean-Rémi Teyssier; Brooke C. Bodle; Alison Ferver; Richard A. Mudarra; Bin Zuo; Travis Tabler; Derrell T. Lee; Craig W. Maynard; et al. (Advances in Food Technology and Nutrition Sciences, 2020)
The research-teaching nexus is the pinnacle of academic activity. As a scientist and educator, my overall objective is to give students access to cutting-edge research and help them develop high order inquiry skills. In addition, as research and thesis writing frequently involves the development of new complex reading skills associated with comprehension and synthesis of a tremendous volume of information, along with in-depth critical analysis, evaluation, and elegant academic writing style, I decided to assign this editorial to my 2020-Biochemical Nutrition graduate students. As my students have diverse educational and cultural backgrounds and have been exposed to a variety of tech-based learning, we decided to summarize here recent advances in omics research in avian species to facilitate the discussion by asking new questions, which may help open new vistas for future investigations. By following the “scaffolded” approach, my students highlighted progress in Transcriptomics (Komp M and Bowie R), Proteomics (Tabler T and Lee T), Kinom-ics (Hernandez RM and Zuo B), Epigenomics (Ferver A), Metabolomics (Maynard C and Mullenix G), and Microbiomics (Teyssier JR and Bodle B). I would like to thank my students for their motivation, dedication, determination, perseverance, connection, consistency, and support. I would also like to thank AFTNS-OJ for inviting me to write this editorial and I hope by getting my students involved would promote their curi-osity, help them understand complex questions, explore more sources, stimulate their independent thinking, and create research- and question-mindsets.